The Correlates of State Policy and the Structure of State Panel Data. Issue 4 (2nd December 2021) - Grossmann, Matt; Jordan, Marty P.; McCrain, Joshua
Abstract: The American states offer a wealth of variation across time and space to understand the sources, dynamics, and consequences of public policy. As laboratories of socioeconomic and political differences, they enable both wide-scale assessments of change and studies of specific policy choices. To leverage this potential, we constructed and integrated a database of thousands of state-year variables for designing and executing social research: the Correlates of State Policy Project (CSPP). The database offers one-stop shopping for accurate and reliable data, allows researchers to assess the generalizability of the relationships they uncover, enables assessment of causal inferences, and connects state politics researchers to larger research communities. We demonstrate CSPP's use and breadth, as well as its limitations. Through an applied empirical approach familiar to the state politics literature, we show that researchers should remain attentive to regional variation in key variables and potential lack of within-state variation in independent and dependent variables of interest. By comparing commonly used model specifications, we demonstrate that results are highly sensitive to particular research design choices. Inferences drawn from state politics research largely depend on the nature of over time variation within and across states and the empirical leverage it may or may not provide.